Identification of PANoptosis associated lncRNAs associated with clinical prognosis and immune infiltration microenvironment in colon adenocarcinoma - Yangyang Wang; Shihui Zhao; Songtao Du; Tianyi Xia; Liqiang Song; Mingyu Xia; Bomiao Zhang (Discover Oncology)
Abstract Early diagnosis and disease management based on risk stratification have a very positive impact on colon adenocarcinoma (COAD) prognosis. It is of positive significance to further explore risk stratification of COAD patients and identify predictive molecular biomarkers. PANoptosis is defined as a form of inflammatory cell death regulated by PANoptosome, with common features of pyroptosis, apoptosis and necroptosis. The role of PANoptosis in COAD has not been fully studied. In this study, we analyzed significant differences in the expression of PANoptosis-related gene (PRG) features in COAD. Subsequently, the PANoptosis associated lncRNAs (PALs) associated with PRGs were analyzed by LASSO algorithm and multivariate Cox analysis, and PALs related to the prognosis of COAD were selected. Based on the expression patterns of prognostic PAL features, we performed unsupervised consensus cluster analysis to categorize COAD samples into distinct PAL molecular subtypes and investigate their associated immune infiltration characteristics. We subsequently constructed PAL score model based on prognostic characteristics and verified its independent prognostic value for COAD. The nomogram diagnostic model was established to confirm the prognostic value of PAL scoring system again. Pathway enrichment analysis, somatic mutation profiling, and drug sensitivity analysis were employed to comprehensively assess the clinical value of the PAL score. Additionally, qRT-PCR was used to further validate the abnormal expression of the selected targets in COAD. Our results provide a new idea for clinical risk stratification and new evidence for the role of PANoptosis in COAD.